CO2 fed microalgae cultivation in photobioreactor: Review on challenges and possible solutions - Emmanuel Yahaya; Wan Sieng Yeo; Jobrun Nandong; Joyce Chen Yen Ngu (Taylor & Francis, 2025)
Carbon dioxide (CO2) sequestration and upgrading algal development rates are basic procedures for moderating climate alter. One of the major challenges in photobioreactors (PBRs) is the successful expulsion of broken-down oxygen (DO), which can hinder algal development and diminish CO2 sequestration proficiency. This ponder highlights the pressing request for maintainable vitality arrangements within the confront of asset exhaustion and heightening CO2 outflows. Microalgae, with their capability for fast development and effective photosynthesis, speak to a promising renewable vitality source and a compelling implication for mechanical CO2 retention. Whereas much inquire has centred on the natural characteristics of microalgae, this consider addresses the often-overlooked control instruments fundamental for moving forward PBR plan and execution. To handle the issue of DO expulsion and optimize microalgae development, a complex control framework coordination sensors and energetic input components is proposed. By checking parameters such as pH, DO, temperature, and CO2 levels, the framework points to improving algal development and CO2 take-up, clearing the way for more viable and feasible PBR frameworks.